Coordination dependence of hyperfine fields of 5sp impurities on Ni surfaces - P. Mavropoulos (JOURNAL OF PHYSICS-CONDENSED MATTER, 2003)
We present first-principles calculations of the magnetic hyperfine fields H-hf of 5sp impurities on the (001), (111), and (110) surfaces of Ni. We examine the dependence of H-hf on the coordination number by placing the impurity in the surfaces, on top of them at the adatom positions, and in the bulk. We find a strong coordination dependence of H-hf, different and characteristic for each impurity. The behaviour is explained in terms of the on-site s-p hybridization as the symmetry is reduced at the surface. Our results are in agreement with recent experimental findings.